2023
DOI: 10.3390/antiox12081516
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Attenuates Particulate Matter-Induced Senescence of Skin Keratinocytes

Kyoung Ah Kang,
Mei Jing Piao,
Pincha Devage Sameera Madushan Fernando
et al.

Abstract: Skin is a direct target of fine particulate matter (PM2.5), as it is constantly exposed. Herein, we investigate whether Korean red ginseng (KRG) can inhibit PM2.5-induced senescence in skin keratinocytes. PM2.5-treated human keratinocyte cell lines and normal human epidermal keratinocytes showed characteristics of cellular senescence, including flat and enlarged forms; however, KRG suppressed them in both cell types. Moreover, while cells exposed to PM2.5 showed a higher level of p16INK4A expression (a senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This connection has spurred scientific research into bioactive agents, known as senolytics, with a focus on natural food resources. Previous studies have reported the preventive effects of RG on cellular senescence in skeletal muscle, skin, and vascules [28][29][30]. However, the impact of RG on cellular senescence in the aged liver remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This connection has spurred scientific research into bioactive agents, known as senolytics, with a focus on natural food resources. Previous studies have reported the preventive effects of RG on cellular senescence in skeletal muscle, skin, and vascules [28][29][30]. However, the impact of RG on cellular senescence in the aged liver remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng, as the most popular cosmetical botanical materials, was found has better skincare activities after appropriate heat treatment [9,10]. During the evaporating process, hydrolysis, isomerization, and decarboxylation degradation reactions could occur simultaneously or solely, for instance, the major ginsenosides which is the most functional ingredients in ginseng could be converted the into rare ginsenosides , the activities are thus getting better [11].…”
Section: Introductionmentioning
confidence: 99%